Embryo Biopsy Can Offer More Information Than Just Ploidy Status - Lal, Arnav; Roudebush, William E.; Chosed, Renee J. (Frontiers in Cell and Developmental Biology, 2020)
As a byproduct of increasing infertility cases, the use of Medically Assisted Reproduction (MAR) has increased. As such, the need to gain information regarding the implantation potential of specific MAR preimplantation embryos prior to transfer has become increasingly critical. One potential source of this information is contained in the blastocoel fluid from day 5/6 embryos. This fluid contains cell-free DNA, proteins, RNA, metabolites, exosomes, etc. and analysis of these contents provides clinicians with an opportunity to gain more data regarding potential of each embryo. While application of preimplantation genetic testing for aneuploidies (PGT-A) may be limited to women of advanced maternal age or with recurrent pregnancy loss, the fluid taken at the time of embryo biopsy can be analyzed for any frozen embryo as well as PGT-A embryos. In both cases, blastocoel fluid analysis provides information regarding a preimplantation embryo’s potential for implantation. Moreover, as remnants of apoptosis, embryonic cell-free DNA and mRNA may lead clinicians to better understand and predict the extent of self-correction occurring within the preimplantation embryo. While analysis of blastocoel components are not yet viable replacements for PGT-A, their study may still reveal critical clinical information about the implantation potential for any given embryo.